An Islamic Economic Perspective on the Indonesian Economy - Yuni Agustin; Hudallah Hudallah (Penerbit Hellow Pustaka, 2026)
The increasing complexity of the global economy requires each country to establish an economic system that is stable, equitable, and sustainable. Indonesia, as the country with the largest Muslim population in the world, has significant potential to develop Islamic economics as a driving force of its national economy. Islamic economics is based on the teachings of the Qur’an and Hadith, aiming to achieve comprehensive societal welfare through the principles of justice, balance, and equitable wealth distribution. Instruments such as zakat, waqf, and the prohibition of wealth hoarding play an important role in reducing social inequality, supported by the growth of the halal industry, Islamic finance, Islamic capital markets, and Sharia-based microenterprises. However, its implementation still faces challenges, including low public literacy, suboptimal regulation, and uneven infrastructure readiness. Therefore, comprehensive strategies are needed to optimize the role of Islamic economics in strengthening national economic stability.